INTEGRASI TEKNOLOGI DIGITAL DALAM TRANSFORMASI SUPERVISI AKADEMIK: SYSTEMATIC LITERATURE REVIEW - Sutrisno; Desnora, Beni; Firmansyah, Alief; Iryani, Eva; Muspawi, Mohamad; Denmar, Denny (Information Technology Education Department, 2026)
The development of digital technology has driven transformation in academic supervision practices; however, its implementation in schools remains largely conventional, administrative, and not yet optimal in supporting teachers’ professional development. This study aims to analyze the transformation of academic supervision through the integration of digital technology based on empirical research findings over the past ten years. This study employs a Systematic Literature Review (SLR) approach, consisting of identification, screening, eligibility, and inclusion stages based on PRISMA guidelines. The findings indicate that the integration of digital technology in academic supervision contributes to four main aspects: improving the efficiency of supervision implementation, strengthening documentation and learning monitoring, enhancing teachers’ professional competence and digital literacy, and transforming supervision models into more flexible, collaborative, and adaptive approaches. Therefore, the integration of digital technology in academic supervision not only functions as a technical support tool but also serves as a strategic approach to improving the quality of learning and teachers’ professionalism in the digital era.